KONFLIK BATIN PADA TOKOH UTAMA WIGATI DALAM NOVEL KHILMA ANIS KAJIAN PSIKOLOGI SASTRA - Zainuddin, Ach; Salamet; Wahedi, Slamet (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the inner conflict experienced by the main character, Wigati, in a novel written by Khilma Anis using a literary psychology approach. This research employs a qualitative descriptive method. The data source of this study is a novel by Khilma Anis that features Wigati as the main character, while the research data consist of words, sentences, dialogues, and narrative passages that indicate the character’s inner conflicts. The data were collected through reading and note-taking techniques by carefully examining the novel and identifying sections related to the inner conflict of the main character. The collected data were analyzed through the stages of data reduction, data presentation, and conclusion drawing based on the concepts of literary psychology. The findings reveal that Wigati experiences several forms of inner conflict, including conflict between personal desires and social expectations, conflict between feelings and moral values, conflict between hopes and reality, and conflict in decision-making. These conflicts reflect the complex psychological dynamics of the character and play an important role in shaping the character’s development throughout the storyline. Through the inner conflicts experienced, Wigati demonstrates a process of self-reflection in facing various life problems.